A prospective, randomized trial comparing the use of KTP (GreenLight) laser versus electroresection-supplemented laser in the treatment of benign prostatic hyperplasia - Torz, Cezary (Cent European J Urol, 2016)
INTRODUCTION: Photoselective laser vaporization of the prostate (PVP) is one of the most popular techniques of treatment of benign prostatic hyperplasia (BPH). The aim of this study was to assess the risk of thermal damage to the external urethral sphincter during PVP at distal part of prostatic urethra. MATERIAL AND METHODS: 66 men submitted to PVP with 80-W Green Light Laser were randomly assigned to receive standard PVP only (group A) or PVP in proximal part followed by transurethral resection in distal part of prostatic urethra (group B). Primary end-points of the study assessed at baseline, 24 hours and 8 weeks after the surgery were: urinary continence, urinary flow (Qmax), post void urine retention (PVR), international prostate symptom score (IPSS), quality of life (QoL). RESULTS: Per protocol analysis was eventually performed in 60 patients. Study groups did not differ in age, preoperative continence, values of Qmax, PVR, IPSS, QoL, or the rate of complete urinary retention (p >0.05). During the 8-week follow-up no patient reported urinary incontinence, while decrease in IPSS (16.3 vs. 14.9, p >0.05), QoL improvement (4.7 vs. 4.7, p >0.05), increase in Qmax (18.2 vs. 17.4, p >0.05) were similar in both study groups. Patients assigned to group B were more likely to have bleeding complications (85.2% vs. 18.2%), including patients requiring transfusion (14.8% vs. 0%). Moreover, postoperative catheterization time was shorter in group A (29.1 hrs vs. 37.2 hrs, p = 0.04). CONCLUSIONS: Laser vaporization for treatment of BPH is safe and effective, with no significant effect on the risk of urinary incontinence in comparison to traditional methods.